Are We Ready for Migrastatics? - Solomon, Jonathan; Raškova, Magdalena; Rösel, Daniel; Brábek, Jan; Gil-Henn, Hava (Cells, 2021)
Metastasis accounts for the highest mortality rates in solid tumor cancer patients. However, research and development have neglected this most lethal characteristic and, instead, have concentrated on the hallmarks of cancer that make tumor cells highly proliferative and distinctive from nonmalignant cells. The concentration on invasion and metastasis can be one of the most meaningful advancements in cancer investigation. Importantly, metastasis-free survival (MFS) was recently approved by the Food and Drug Administration (FDA) as a novel primary endpoint in clinical trials and has been used to evaluate the prognosis of patients with nonmetastatic castration-resistant prostate cancer and soft tissue sarcoma. This new definition enables to shift the focus of research and development in cancer therapeutics toward metastasis and to change the emphasis from using tumor shrinkage as a benchmark for indicating the efficacy of treatment to using MFS as a more representative endpoint for antimetastatic drugs. This perspective outlines the possibility to use this novel endpoint in other solid cancers, and examples of large clinical trials are given in which MFS is defined as an endpoint and/or in which antimetastatic strategies are being examined. These advances now open the door for the rapid development of antimetastatic therapies, which could be used in combination with standard cytotoxic cancer therapies. With pioneer research on metastasis prevention on the rise and the underlying biomechanisms of tumor cell motility and invasion explored further than ever before, we believe an intensified focus on antimetastatic properties will shape this era of cancer translational research.
Keywords: Neoplasm Invasiveness; lidé; metastázy nádorů; metastasis-free survival; Antineoplastic Agents; Clinical Trials as Topic; Translational Research, Biomedical; protinádorové látky; Research Design; Humans; Progression-Free Survival; doba přežití bez progrese choroby; Neoplasm Metastasis; research and development; Cell Movement; nádory; cancer metastasis; metastasis inhibitor; zvířata; pohyb buněk; klinické zkoušky jako téma; translační biomedicínský výzkum; Animals; Endpoint Determination; invazivní růst nádoru; stanovení cílového parametru; výzkumný projekt; clinical trials; Neoplasms